2013
DOI: 10.4236/crcm.2013.24075
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic (heterotopic) pancreas in the mesentery of the jejunum: Imaging findings

Abstract: Ectopic pancreatic tissue in the mesentery of the jejunum is an entity that is seen very rarely. Most patients are asymptomatic and usually this is an incidental finding at autopsy or laparotomy. Most of the cases are clinically silent, but symptoms either might be due to the localization of the ectopic tissue or due to the complications including obstruction or bleeding. Surgery is not indicated unless complications occur, so diagnosis is very important for prevention of unnecessary surgery. Here, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…17 Typical findings were central umbilication and rolling sign under endoscopy and a low echogenicity under EUS. 17,18 In our case, PH was mistaken for adhesion on CT scan, but a protruding mass with typical endoscopic features was found using SBE afterward. In our literature review, some PHs were only confirmed or incidentally detected by surgery (n = 28, 15.7%), especially in the ileum subgroup (n = 9/26, 34.6%; Fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…17 Typical findings were central umbilication and rolling sign under endoscopy and a low echogenicity under EUS. 17,18 In our case, PH was mistaken for adhesion on CT scan, but a protruding mass with typical endoscopic features was found using SBE afterward. In our literature review, some PHs were only confirmed or incidentally detected by surgery (n = 28, 15.7%), especially in the ileum subgroup (n = 9/26, 34.6%; Fig.…”
Section: Discussionmentioning
confidence: 62%
“…However, it was suggested that using secretin during MRI might improve the visualization of this sign 17 . Typical findings were central umbilication and rolling sign under endoscopy and a low echogenicity under EUS 17,18 . In our case, PH was mistaken for adhesion on CT scan, but a protruding mass with typical endoscopic features was found using SBE afterward.…”
Section: Discussionmentioning
confidence: 63%
“…Tai galėtų paaiškinti, kodėl dauguma EK būna aplink kasą, daugiausiai virškinamajame trakte, skrandyje, dvylikapirštėje žarnoje, proksimalinėje tuščiosios žarnos dalyje (18). EK paprastai yra izoliuotas pažeidimas, tačiau galima aptikti ir kitų lokalizacijų pažeidimų (19). …”
Section: Diskusijaunclassified
“…MRT signalo charakteristikos ir kontrastinės medžiagos kaupimo pobūdis yra tokie patys kaip normalaus kasos audinio. MRT tyrimas padeda vizualizuoti ektopinio kasos audinio latakėlių sistemą (19). Magnetinio rezonanso cholangiopankreatografija (MRCP) gali išryškinti patognominį EK požymį – latakėlius, taip patvirtindama tikslesnę priešoperacinę diagnozę (12).…”
Section: Diskusijaunclassified
See 1 more Smart Citation